Use of -Based Interactive Learning Media Visuals in Science Learning - Hasanah, Uswatun; Sudira, Putu (Universitas Pendidikan Ganesha, 2021)
The fundamental problem in implementing education at the education level is that the learning process is generally too oriented to mastery of subject matter, not to the substance, meaning, or value it contains. This study aims to analyze the success of using visual-based interactive media or image media in science learning. This type of research is an actual experiment with a quantitative approach. The subjects in this study were 50 students consisting of 2 separate classes, the number of female students was 30, and the number of male students was 20. The method of data collection in this study used student learning outcomes pre-test and post-test. The instrument used is a test of learning outcomes and student response questionnaires. The technique used to analyze the data is the descriptive qualitative and quantitative analysis and inferential statistics. The results showed that the average score of learning science after using visual-based interactive learning media was 75.93, with a standard deviation of 16.19. The lowest score for students is 40, and the highest score is 99. Visual-based interactive media is effectively used to improve student learning outcomes in science. The research implication is that visual-based interactive media can be used by teachers in teaching so that they can help students learn.